The use of brick waste as coarse aggregates partial replacement in concrete production - Najmuddin, Nordin (2014)
Issue related to the scarcity of good and quality of coarse aggregate has kept the construction industries into a crisis in findings an alternative to overcome this situation. The issue is worsening as the current aggregate used in the construction industries are non-renewable aggregates from the quarrying activities. Fast development in the recent years indeed has increased the need of coarse aggregate in the alarming rate. Besides that, the growth of the construction industry has also produced lots of product mainly the waste materials. In fact, land filling is the most common waste management practice in Malaysia. The high amount of construction waste generated from the construction industries has caused a scarcity of the landfill area. The study is conducted to investigate the use of brick waste as a coarse aggregate replacement in concrete production. The aim of this study is to determine the suitability of brick waste as partial replacement of coarse aggregate in concrete production. Furthermore, to investigate the mechanical and physical properties of brick waste concrete, and to compare the performance of brick waste as partial replacement of coarse aggregate in concrete with the conventional concrete (control sample). In order to fulfil the objective, there are tests that were conducted to determine concrete performance, such as compressive strength test, flexural test, and water penetration test. The data were collected and analyzed to satisfy the study on brick waste as an alternative in coarse aggregate partial replacement in concrete production. With the different mix proportion in percentages of the brick waste as coarse aggregate replacement of, 0, 5.0, 7.5, 10.0 and 12.50% in the equivalent strength of grades 25, the result was analyzed. From the results, it indicates that the optimum strength was achieved at 5.0% brick waste mix proportion and higher compared with the control sample, 0% brick waste mix proportion. The results also indicate that the optimum strength of brick waste concrete has achieved the grade 25 of concrete.